Realidade e representação no romance regionalista brasileiro: tradição e atualidade - Santini, Juliana [UNESP] (My University, 2014)
This work presents a discussion on Brazilian regionalist novel and its relationship to representation of reality along of Brazilian history of literature. Under this point of view, this article analyzes how the novel Galileia, by Ronaldo Correia de Brito, retakes, refuses or brings up to date, in contemporary prose, some aspects that established this kind of production inside literary diachrony in Brazil.

Este trabalho apresenta uma discussão em torno do romance regionalista na história da literatura brasileira e sua relação com a representação do real. Sob essa perspectiva, analisa-se de que modo o romance Galileia, de Ronaldo Correia de Brito, retoma, atualiza ou recusa, na prosa contemporânea, aspectos que determinaram esse tipo de produção ao longo da diacronia literária brasileira.
Reality and representation in Brazilian regionalist novel: the tradition and the present
Keywords: Regionalist novel; Representation; Contemporary narrative; Regionalismo; Literatura brasileira; Prosa brasileira contemporânea